2008
DOI: 10.1039/b718788b
|View full text |Cite
|
Sign up to set email alerts
|

Structures and interaction energies of stacked graphene–nucleobase complexes

Abstract: The noncovalent interactions of nucleobases and hydrogen-bonded (Watson-Crick) base-pairs on graphene are investigated with the DFT-D method, i.e., all-electron density functional theory (DFT) in generalized gradient approximation (GGA) combined with an empirical correction for dispersion (van der Waals) interactions. Full geometry optimization is performed for complexes with graphene sheet models of increasing size (up to C(150)H(30)). Large Gaussian basis sets of at least polarized triple-zeta quality are em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
240
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(266 citation statements)
references
References 76 publications
(96 reference statements)
25
240
1
Order By: Relevance
“…The interaction strengths of the different bases with graphene vary as it depends on the polarizability of the DNA bases [93,95]. Both theoretical and experimental studies report that guanine binds most strongly to graphene while A, T and C have lower and similar interaction strengths [93,[96][97][98][99][100].…”
Section: Detection Methods Based On Dna Adsorptionmentioning
confidence: 99%
“…The interaction strengths of the different bases with graphene vary as it depends on the polarizability of the DNA bases [93,95]. Both theoretical and experimental studies report that guanine binds most strongly to graphene while A, T and C have lower and similar interaction strengths [93,[96][97][98][99][100].…”
Section: Detection Methods Based On Dna Adsorptionmentioning
confidence: 99%
“…31 Previous work has focused on characterization of the adsorption of single nucleotides or nucleosides by atomic force microscopy (AFM), 32 isothermal titration calorimetry, 33 and theoretical calculations. [34][35][36] It was concluded that non-electrostatic interactions dominate the binding, 32 and the purine bases bind more strongly than the pyrimidines. 33,35,36 The adsorption of DNA on carbon nanotubes has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] It was concluded that non-electrostatic interactions dominate the binding, 32 and the purine bases bind more strongly than the pyrimidines. 33,35,36 The adsorption of DNA on carbon nanotubes has also been studied. [37][38][39][40][41][42][43] GO and nanotubes, however, are fundamentally different and the adsorption/desorption of oligonucleotides on GO have not been systematically tested as a function of solution conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Waals interactions are accounted for by using an empirical correction method 29 . This method has been proven to be effective in describing layered materials [30][31][32] . We have checked that the atomic displacements due to extra doped charges or vertical external electric fields considered in our work are less than 0.5 % of the bond lengths (since the material is not polar).…”
mentioning
confidence: 99%